The effects of arginine phosphate (ArGrow® Granulat) on growth of Scots pine and Norway spruce seedlings planted in varying soil layer structures simulating site preparation - Luoranen, Jaana; Saksa, Timo (Oxford University Press (OUP), 2024)
The pressure to plant seedlings in unprepared instead of prepared soil in forest regeneration is increasing, although seedlings’ growth in unprepared soil is poorer. One way to improve seedlings’ growth could be to add arginine phosphate to the planting hole at the time of planting. In field studies, abiotic and biotic damage normally disturbs studies which seek to determine growth effects, especially in unprepared soil. The study’s aims were (i) to clarify whether it was possible to investigate the differences between varying soil layer structures mimicking site preparation methods and seedling treatments in simulated planting places in partly controlled conditions; and (ii) to investigate the effects of arginine phosphate (arGrow® Granulat) on the growth, especially root growth, of Norway spruce (Picea abies (L.) H. Karst.) and Scots pine (Pinus sylvestris L.) container seedlings in those simulated planting places. Seedlings of both tree species were planted in 40 l pots sunk partly into the soil in a sandy field. Before planting, pots were filled with soil layers mimicking layers in soil without any site preparation treatment and in spot mounds. After one growing season, the differences in growth parameters between treatments were small in Norway spruce seedlings, and no significant benefits of arginine phosphate were observed. The soil in the spruce pots was fine-textured and contained a thick organic layer. More studies in more common forest soil types suitable for Norway spruce seedlings are needed to be sure about the growth responses. In Scots pine seedlings, adding arginine phosphate granules to the planting holes improved the growth of seedlings at least in the first summer after planting in soil layers mimicking no mechanical site preparation situation, and the growth improvement may even have compensated the mounding effects. In conclusion, mimicking site preparation methods in large pots was a promising method by which the differences between site preparations methods as well as effects of seedling treatments, in our case arginine phosphate, on the growth of conifer seedlings, can be tested.
Keywords: metsäkuusi; metsämänty; maanmuokkaus; istutus (kasvit); Picea abies; Pinus sylvestris; mechanical site preparation; planting; nutrient concentrations